FORMULATION AND EVALUATION OF MANALAGI APPLE PEEL (Malus sylvestris Mill) SUNSCREEN SPRAY AS HALAL COSMETICS - Ginanjar Putri Nastiti; Faradillah Maulida; Agisha Salwa Salsabila (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Manalagi apple peel is known to contain flavonoid compounds that are active as photoprotectors, as well as antioxidants that can absorb UV-A and UV-B exposure and release free radicals. Apple peel has the potential to be formulated as an active ingredient in natural sunscreen, which is considered safer and less likely to irritate when applied to the peel. In this study, halal sunscreen preparations from 70% ethanol extracts of manalagi apple peel with varying concentrations of manalagi apple peel extract were 15%, 20%, and 25%. The purpose of this study was to determine the critical halal point of sunscreen spray preparation, physical characteristics (organoleptic, homogeneity, pH, viscosity, and spray pattern), and SPF value. The data analysis methods in this study were descriptively and quantitatively performed. Based on the results of this study, no halal critical point ingredients were used in the formulation. The physical characteristic test results of all spray sunscreen formulas met the requirements of good physical characteristics criteria, and the resulting SPF values of F1, F2, and F3 were 22.66, 26.51, and 31.22, respectively. The SPF value of the Manalagi apple peel waste sunscreen spray formula was very high (>15).    Keywords: Halal, cosmetics, manalagi apple peel, SPF, spray sunscreen